Engrailed 2 (EN2) acts as a glioma suppressor by inhibiting tumor proliferation/invasion and enhancing sensitivity to temozolomide - Li, Tengfei (Cancer Cell Int, 2020)
BACKGROUND: Glioma is one of the most malignant brain tumors and accounts for the majority of brain cancer related death. Despite progress on mechanistic studies, current understandings of the initiation and progression of glioma are still incomplete. Previous studies demonstrate that Engrailed-2 (EN2), a homeobox-containing transcription factor, is associated with tumorigenesis in a range of cancers heterogeneously, however, the profiles of EN2 expression and its potential functions in gliomas remain unclear. METHODS: Real-time PCR was used to identify the expression of EN2 in glioma tissues. To study the biological function of EN2 in glioma, we compared the cell viability and proliferation profiles between EN2 overexpressed and control cells using cell counting kit-8 (CCK8) assay, EdU incorporation assay and colony formation assay. Flow cytometry and Hoechst staining assays were performed to investigate the role of EN2 on glioma cell death. Finally, wound healing and transwell assays were carried out to investigate the role of EN2 on glioma cell invasion. RESULTS: We identified that EN2 was downregulated in human gliomas compared with paired adjacent normal tissues and negatively associated with glioma malignancy. Elevated EN2 expression inhibits cell proliferation, enhances glioma sensitivity to temozolomide and inhibits migration/invasion of glioma cells. CONCLUSIONS: Our data identify a novel function of EN2 in glioma suppression and provide potential therapeutic targets for glioma therapy.